Design and real-time implementation of perturbation observer based sliding-mode control for VSC-HVDC systems. (November 2016) - Yang, B.; Sang, Y.Y.; Shi, K.; Yao, Wei; Jiang, L.; Yu, T.
Abstract: This paper develops a perturbation observer based sliding-mode control (POSMC) scheme for voltage source converter based high voltage direct current (VSC-HVDC) systems. The combinatorial effect of nonlinearities, parameter uncertainties, unmodelled dynamics and time-varying external disturbances is aggregated into a perturbation, which is estimated online by a sliding-mode state and perturbation observer. POSMC does not require an accurate system model and only one state measurement is needed. Moreover, a significant robustness can be provided through the real-time compensation of the perturbation. Four case studies are carried out on the VSC-HVDC system, such as active and reactive power tracking, AC bus fault, system parameter uncertainties, and weak AC grid connection. Simulation results verify its advantages over vector control and feedback linearization sliding-mode control. Then a hardware-in-the-loop (HIL) test is undertaken to validate the implementation feasibility of the proposed approach. Abstract : Highlights: Perturbation observer based sliding-mode control (POSMC) design is developed for VSC-HVDC systems. Various system uncertainties are estimated and compensated online. The over-conservativeness of SMC is avoided and the tracking accuracy can be improved. The HIL test validates the implementation feasibility of POSMC.